Attenuation of quorum sensing system and virulence in Vibrio cholerae by phytomolecules - Saha, Subhasree; Aggarwal, Shifu; Singh, Durg Vijai (Frontiers in Microbiology, 2023)
The Vibrio cholerae, a gram-negative bacterium, is the causative agent of cholera. Quorum sensing is a cell-to-cell communication that leads to gene expression, accumulation of signaling molecules, biofilm formation, and production of virulence factors. The quorum sensing pathway in V. cholerae is regulated by luxO, and biofilm formation and other virulence factors are positively controlled by aphA and negatively by hapR. Hence, targeting the global regulator luxO would be a promising approach to modulate the QS to curtail V. cholerae pathogenesis. The present study investigated the modulating activity of quercetin and naringenin on biofilm formation and quorum-sensing regulated phenotypes in V. cholerae. Then after we determined the anti-quorum sensing capability of phytomolecules against the model organism Chromobacterium violaceum. Also, we performed flow cytometry for live/dead bacteria, MTT assay, CLSM, and growth curve analysis to determine their role as QS modulators rather than anti-bacterial. V. cholerae strains VC287 and N16961 formed thick biofilm. We observed a two-fold reduction in the expression of biofilm-associated genes comprising gbpA, vpsA, rbmA, and mbaA in the presence of phytomolecules indicating that phytomolecules modulate quorum sensing pathway rather than killing the bacteria. These phytomolecules were non-toxic and non-hemolytic and had anti-adhesion and anti-invasion properties. In addition, quercetin and naringenin were found to be highly effective compared to known quorum-sensing inhibitors terrein and furanone C-30. Thus, this study provides evidence that phytomolecules: quercetin and naringenin modulate the quorum-sensing pathway rather than killing the bacteria and can be used as an anti-quorum-sensing molecule for therapy against the pathogen.